2014
DOI: 10.1128/jvi.00570-14
|View full text |Cite
|
Sign up to set email alerts
|

H7N9 and Other Pathogenic Avian Influenza Viruses Elicit a Three-Pronged Transcriptomic Signature That Is Reminiscent of 1918 Influenza Virus and Is Associated with Lethal Outcome in Mice

Abstract: Modulating the host response is a promising approach to treating influenza, caused by a virus whose pathogenesis is determined in part by the reaction it elicits within the host. Though the pathogenicity of emerging H7N9 influenza virus in several animal models has been reported, these studies have not included a detailed characterization of the host response following infection. We found that responses to the H7 subtype viruses were intermediate to those elicited by H5N1 and pdm09H1N1 early in infection but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 66 publications
(116 reference statements)
9
41
0
Order By: Relevance
“…As of 23 June 2015, the laboratory-confirmed case-fatality rate of A(H7N9) virus infection was 41%, which was lower than that of A(H5N1) infection (53%) but much higher than that in the 2009 pandemic caused by the A(H1N1)pdm09 virus (ϳ0.1 to 5%) (5,6). In mice, the virulence of A(H7N9) virus is between that of the highly pathogenic A(H5N1) and A(H1N1)pdm09 viruses (7,8). A transcriptomic study also showed that the perturbation of the host gene expression profile of A(H7N9) virus infection is intermediate to that of A(H5N1) and A(H1N1)pdm09 virus infections (7).…”
mentioning
confidence: 95%
“…As of 23 June 2015, the laboratory-confirmed case-fatality rate of A(H7N9) virus infection was 41%, which was lower than that of A(H5N1) infection (53%) but much higher than that in the 2009 pandemic caused by the A(H1N1)pdm09 virus (ϳ0.1 to 5%) (5,6). In mice, the virulence of A(H7N9) virus is between that of the highly pathogenic A(H5N1) and A(H1N1)pdm09 viruses (7,8). A transcriptomic study also showed that the perturbation of the host gene expression profile of A(H7N9) virus infection is intermediate to that of A(H5N1) and A(H1N1)pdm09 virus infections (7).…”
mentioning
confidence: 95%
“…The decreased transcription of coagulation and lipid metabolism genes identified in the mouse study was not identified in Calu3 cells indicating that it is likely driven by nonepithelial cell types or by the crosstalk between multiple cell types in the lung. Strikingly, this gene expression signature also occurs in the whole lung response to the infamous 1918 H1N1 virus, indicating that it may predict pathogenicity across different strains [15]. Experiments in cynomolgus macaques confirmed the validity of the pathways and molecules identified in the H7N9 mouse model [16].…”
mentioning
confidence: 51%
“…Transcriptional responses to H7N9 were intermediate to those caused by pH1N1 and H5N1 early in infection, but grew to resemble the H5N1 response as infection progressed. Infection with H5N1, H7N7 and H7N9, which are lethal in mice, increased transcription of cytokine response genes and decreased transcription of coagulation and lipid metabolism genes [15]. The decreased transcription of coagulation and lipid metabolism genes identified in the mouse study was not identified in Calu3 cells indicating that it is likely driven by nonepithelial cell types or by the crosstalk between multiple cell types in the lung.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Based on results from BALB/c mice challenged with isogenic chimeric AIVs, the H7 subtype demonstrated a potential to cause enhanced disease in mammals (17). H7N7 and H7N9 viruses of human origin can also induce a transcriptomic response resulting in increased pathogenicity in BALB/c mice (18).…”
mentioning
confidence: 99%